2005
DOI: 10.1007/s10722-003-6012-x
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of Escontria chiotilla in Wild and Silvicultural Managed Populations in the Tehuacán Valley, Central Mexico

Abstract: Escontria chiotilla is a columnar cactus that grows in the arid and semiarid lands of Central Mexico and produces edible fruit with economic. In the wild, this plant species is distributed as part of thorn-scrub and tropical deciduous forests, but in the Tehuaca´n Valley also occurs in silvicultural managed in situ populations, in which people practise artificial selection enhancing phenotypes with larger fruits. The population genetics of wild and managed populations was studied to analyse the effects of mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
2
25
1
1
Order By: Relevance
“…Agricultural management involves clearing from the fields tolerating individuals of Escontria chiotilla and other 35 species of useful plants (Arellano and Casas 2003;Vivar 2004). Morphological and population genetics studies (Arellano and Casas 2003;Tinoco et al 2005) revealed patterns of artificial selection and gene flow similar to those referred to above for Polaskia spp. (3) Garambullal, a forest type dominated by Myrtillocactus schenckii (370 ind./ha) occurring at elevations from 600 to 2,100 m on volcanic soils, in the territory of Santiago Coatepec.…”
Section: Study Sitessupporting
confidence: 52%
See 1 more Smart Citation
“…Agricultural management involves clearing from the fields tolerating individuals of Escontria chiotilla and other 35 species of useful plants (Arellano and Casas 2003;Vivar 2004). Morphological and population genetics studies (Arellano and Casas 2003;Tinoco et al 2005) revealed patterns of artificial selection and gene flow similar to those referred to above for Polaskia spp. (3) Garambullal, a forest type dominated by Myrtillocactus schenckii (370 ind./ha) occurring at elevations from 600 to 2,100 m on volcanic soils, in the territory of Santiago Coatepec.…”
Section: Study Sitessupporting
confidence: 52%
“…Also noteworthy is the capability of agroforestry systems studied to maintain or even enhance the abundance of some endemic species of high cultural values, such as Escontria chiotilla, Polaskia chende, and P. chichipe. In addition, it is remarkable that, on average, nearly 94% of genetic diversity of wild populations of the main columnar cacti species composing natural forests is maintained within agroforestry systems (Tinoco et al 2005, Parra et al 2008.…”
Section: Biodiversity Conservation In Agroforestry Systems Of the Tehmentioning
confidence: 99%
“…Recent studies have documented that some of these management practices have had some effect on the populations of various species, which can be interpreted as forms of incipient domestication. Among these species are the columnar cacti Escontria chiotilla, Pachycereus hollianus, Polaskia chende, P. chichipe, Stenocereus stellatus, S. pruinosus (Casas et al 1997b(Casas et al , 1999b(Casas et al , 1999cCruz and Casas 2002;Arellano and Casas 2003;Otero-Arnaíz et al 2003, 2005a, 2005bCarmona and Casas 2005;Tinoco et al 2005;Oaxaca-Villa et al 2006;Rodríguez-Arévalo et al 2006;Ruíz-Duran 2007), as well as species of other plant groups such as Sideroxylon palmeri (Sapotaceae) (González-Soberanis and Casas 2004), Ceiba aesculifolia ssp. parvifolia (Bombacaceae) (Avendaño et al 2006), and Proboscidea louisianica spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heterozygote deficits in tropical plants have been found in populations of Piper amalago (Heywood and Fleming, 1986), Austromyrtus spp. (Shapcott and Playford, 1996), Syzygium nervosum (Shapcott, 1998), Ancistrocladus korupensis (Foster and Sork, 1997), Capsicum annuum (Hernández-Verdugo et al, 2001), Escontria chiotilla (Tinoco et al, 2005) and the dioecious species Chamaedorea tuerckheimii, Carica papaya and Carica cauliflora (Oyama et al, unpublished data). Inbreeding was also detected in populations of the trees Pithecellobium pedicellare (O'Malley and Bawa, 1987) and Bertholletia excelsa (O'Malley et al, 1988).…”
Section: Discussionmentioning
confidence: 99%